The biographer and the subject : a study on biographical distance - Tekcan, Rana (Studies in English literatures, 2010)
A good biography is a well-staged illusion. It createson papera vivid, rounded, and immediate sense of lived life. In contrast to purely fictional forms, biography writing does not allow total freedom to the biographer in the creative act. Ideally, a biography's backbone is formed by accurate historical facts. But its soul lies elsewhere. Since the concern is life, something more is needed: Nothing dry, cold or dead, but a vibrant impression of life that is left in the air after one turns over the last page. But how does a biographer do it? The way a biographer creates a subject is largely d.